Altering gillnet soak duration and timing minimizes bycatch and maintains target catch. - Sydney M Collins; Robert J Blackmore; Jessika Lamarre; Caleb S Spiegel; William A Montevecchi (PLoS ONE, 2025)
Seabirds are one of the most at-risk avian groups worldwide, and incidental catch in fishing practices is one of the top threats for seabirds globally. Seabirds that forage on fish through surface feeding, pursuit-diving, or plunge-diving are particularly vulnerable to bycatch. Bycatch mitigation solutions are therefore a vital component of global seabird conservation, but owing to the episodic nature of bycatch and its involvement of match-mismatch contingencies, results from existing efforts involving gear additions (e.g., lights, flags, or buoys) are highly varied and, at times, reduce target catch. Altering the time during which gear remains in the water and modifying fishing practices based on the activity patterns of target fish and seabirds is a promising option for bycatch mitigation. We experimentally tested best practices for the soak timing and duration of shallow-set gillnets used in the Atlantic herring (Clupea harengus) bait fishery in Newfoundland and Labrador, Canada. We compared catch, bycatch, and seabird activity among control (ca. 24 h) and short (ca. 12 h) set durations that were left to soak overnight or only during daylight hours. Target catch did not differ between control and short overnight sets but was greatly reduced during short daytime sets. Nearly all bycatch, including all seabird bycatch, occurred during the control sets. Seabirds associated with fishing vessels throughout the day. Since the catch of herring in gillnets occurs at night outside of most coastal seabirds' foraging period, we recommend that fishers continue to haul their nets early every morning to minimize the time where shallow-set nets are filled with prey during daytime hours, thereby limiting seabird bycatch risk.